Preparation and Characterization of Light‐Cured Dental Resin without Methacrylate Monomers Derived from Bisphenol A. Issue 3 (7th March 2014) - Yu, Biao; Liu, Dongliang; Liu, Fang; He, Jingwei
ABSTRACT With the growing attention on health, dentistry‐used methacrylate monomers like 2.2‐bis[p‐(2'‐hydroxy‐3'‐methacryl‐oxypropoxy)phenylene]propane (Bis‐GMA), which are derived from bisphenol A (BPA), have been doubted because of the estrogenic effect of BPA. In this research, new BPA‐free dental resin systems urethane dimethacrylate monomer/1, 6‐bis(2'‐methacryloyoxy‐ethoxycarbonyl‐amino)‐2, 4, 4‐trimethylhexane/triethyleneglycol dimethacrylate (UDMTA/UDMA/TEGDMA) were prepared with the aim to replace the commonly used Bis‐GMA/TEGDMA dental resin system. Physicochemical properties such as double bond conversion, volumetric shrinkage, water sorption and solubility, flexural strength, and modulus of new resin systems were studied. The results showed that the new BPA‐free dental resins had comparable or better physicochemical properties when compared with Bis‐GMA/TEGDMA dental resin except for their water sorption that was higher than that of Bis‐GMA/TEGDMA dental resin. Therefore, the BPA‐free UDMTA/UDMA/TEGDMA resin system has potential to be used as a resin matrix of dental materials, but much more studies need to be undertaken in future.